Counterintuitive issues in the charge transport through molecular junctions - Bâldea, Ioan (Physical chemistry, chemical physics, 2015)
Whether at phenomenological or microscopic levels, most theoretical approaches to charge transport through molecular junctions postulate or attempt to justify microscopically the existence of a dominant molecular orbital (MO). Within such single level descriptions, experimental current-voltage I-V curves are sometimes/often analyzed by using analytical formulas expressing the current as a cubic expansion in terms of the applied voltage V, and the possible V-driven shifts of the level energy offset relative to the metallic Fermi energy ε0 are related to the asymmetry of molecule-electrode couplings or an asymmetric location of the “center of gravity” of the MO with respect to electrodes. In this paper, we present results demonstrating the failure of these intuitive expectations. For example, we show how typical data processing based on cubic expansions yields a value of ε0 underestimated by a typical factor of about two. When compared to theoretical results of DFT approaches, which typically underestimate the HOMO-LUMO gap by a similar factor, this may create the false impression of “agreement” with experiments in situations where this is actually not the case. Furthermore, such cubic expansions yield model parameter values dependent on the bias range width employed for fitting, which is unacceptable physically. Finally, we present an example demonstrating that, counter-intuitively, the bias-induced change in the energy of an MO located much closer to an electrode can occur in a direction that is opposite to the change in the Fermi energy of that electrode. This is contrary to what one expects based on a “lever rule” argument, according to which the MO “feels” the local value of the electric potential, which is assumed to vary linearly across the junction and is closer to the potential of the closer electrode. This example emphasizes the fact that screening effects in molecular junctions can have a subtle character, contradicting common intuition.